PAISAJES DE LA MODERNIDAD EN LA PROVINCIA DE BUENOS AIRES: LA OBRA DEL ARQUITECTO FRANCISCO SALAMONE (1936-1940) - Jimena Cruz (Revista de Arqueología Histórica Argentina y Latinoamericana, 2013)
This work seeks to understand the architecture as a part of the materiality of a social landscape and as an active element, produced by a society where he belongs. From this idea I make some considerations about the potential of the studies of the archaeology of architecture as a form of understand different problematics. I propose to illustrate this idea by studying the process of consolidation of the industrial capitalism in the Buenos Aires Province (Argentina) during the 1930 decade through the changes that occurred in the urban landscape of that region. In order to accomplish that, the constructions and buildings designed by the architect Francisco Salamone were studied. They were part of an edification plan developed by the provincial government during the years 1936 to 1940. In this particular work, I consider the city of Azul, localized in the South of the Buenos Aires province where two buildings made by that architect, the cemetery and the slaughterhouse, are present.